Schaum's Signals and Systems Problem 2.5 : Finding a convolution in MATLAB - Berry, Carlotta (McGraw-Hill's AccessEngineering., 2020)
This video will show how to use convolution in MATLAB to find the output for a continuous-time LTI system given the impulse response and input.